An Empirical Study On Sanitization And Cleanliness Practices Followed By Street Food Vendors Of Bodhgaya ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2020)
Background: In the fast paced life of today, where dynamism and easy availability of ‘next  best’ alternative is prevalent, one focuses on keeping himself on his toes every moment of  the day so as to have a niche over the competition. Because of this cut throat reality, the  individual can never focus on secondary activities that are required for a healthy lifestyle,  and one of the most common activities in that would be eating nourishing meals. Rather than  excelling in their professional fields by avoiding other activities like eating properly to save  time, eating such unhealthy food creates diseases which get them to back away from their  work and focus on their weakened immunity which results from such unhealthy eating. It is a  very well known fact that about 40% of the people tend to eat more when they feel stressed.  What quality of ingredients they use, what is the water quality, what are the storing techniques  of raw as well as cooked food are some of the many questions which are better left to the  unambiguous. Objectives: To elucidate the hygiene practices, if any, followed by the street  food vendors. To Analyze the present trend of cleanliness and hygiene at street food carts.  To study about the customer perception towards cleanliness. Methodology: This explorative  study, intends to portray the sanitation procedures and practices followed by the street food  vendors of the city Bodhgaya, which is in the state of Bihar. Results: The data analysis was  done, it was found out that out of a score of 130 the average was 108, with 3 main parameters  of Food, Water and other parameters with 13 sub headings. 20.25 was the average for water  (out of 30), 33.6 were for water (out of 40) and general cleanliness and hygiene levels were  at 49.6 out of 60. Conclusion: The parameters of hygiene were being adhered depending on  the feasibility of the food handler this demands for increasing the awareness and quick checks  by the governing body.
Keywords: Street Food; Sanitization; Cleanliness; Professional Life; Competition